Asas Dominus Litis Bagi Kejaksaan dalam Penuntutan Tindak Pidana Berdasarkan Undang-Undang - Budi Mulya; Ulya Kencana; Cholidi Cholidi; M. Zuhdi (Wajah Hukum, 2022)
The Criminal Procedure Code is a generally accepted procedural law for criminal acts in Indonesia. It is regulated that those who have the right to carry out prosecutions are the Public Prosecutor or the Prosecutor. There is an element of legal uncertainty regarding his authority in prosecuting corruption crimes, for example. The separation of the authority of the Corruption Eradication Commission from the Prosecutor's Office, specifically as a claimant. In fact, the prosecution is on behalf of the Public Prosecutor or the Prosecutor. With the dominus-litis principle, expressly states that there is no other institution other than the Prosecutor as the Public Prosecutor who has the absolute right to sue. This study examines the principle of dominus litis for the prosecutor in the prosecution of criminal acts based on the law. The research method, the type of normative research with a descriptive approach. It was concluded that it was necessary to clarify the position of the Indonesian Prosecutor's Office as an executive agency. According to the rules, the Prosecutor's Office should be under the same roof as the judiciary. or the sake of the presence of legitimacy for the Prosecutor's Office itself. So that there is no uncertainty of authority for the Public Prosecutor in prosecuting criminal cases. Oleh karena itu perlu dibuat peraturan baru terkait dengan Kejaksaan RI untuk menuntut kasus tindak pidana berdasarkan asas dominus litis. Where the Prosecutor's Office is the owner of the dominus litis authority in terms of prosecution.